Exploring health behaviors of pregnant women during the COVID-19 pandemic: A qualitative content analysis - Nasibeh Sharifi; Anvar-Sadat Nayebinia; Afsaneh Raiesifar; Tayebeh Rashidian; Zeinab Raiesifar; Azita Fathnezhad-Kazemi (Tehran University of Medical Sciences, 2023)
Background & Aim: Infectious diseases represent a significant health concern within human communities. Considering the importance of pregnancy, the present study was conducted with the aim of exploring the health behaviors exhibited by pregnant women during the COVID-19 pandemic. Methods & Materials: This qualitative study employed the conventional content analysis approach to examine a cohort of 16 pregnant women in 2021. The research was conducted within the health centers of Ilam, employing the purposeful sampling technique and unstructured interviews to collect the data. Simultaneous to the data collection, conventional content analysis was employed to analyze the data. MAXQDA version 10 software was utilized for data management purposes. Results: The participants had a mean age of 30 years, while the average gestational age was 30.38 weeks. Through analysis, three main themes and eight categories were derived from the collected data. The main themes identified were as follows: 1- self-care practices for disease prevention, 2-  the adverse effects of the pandemic on pregnancy, and 3- changes in the healthcare system. Conclusion: The results of the present study highlight the emergence of a novel form of self-care among pregnant women as a consequence of the COVID-19 pandemic. The adverse effects of the pandemic, such as quarantine measures, were associated with the development of negative ruminations within pregnant women. Following the quarantine restrictions, significant modifications were observed in the ways through which women sought health-related information and engaged in daily activities. Moreover, alterations were made to care policies. Paying attention to the comprehensive health needs of pregnant women, including both physical and mental health, is imperative within the context of pandemic-related health services.